Metode Pembiasaan Dalam Pembinaan Akhlak Anak Usia Dini Di Desa Sumberagung - Fadil, Akhmad Fadillah Isnan; Khoironi; Septia Nugroho, Anggi (Al-Mau'izhoh: Jurnal Pendidikan Agama Islam, 2025)
The moral crisis that occurs in society today is a serious challenge, especially in fostering the character of early childhood. Children at an early age need structured guidance to instill moral and moral values that will shape their personality in the future. This study aims to explore the implementation of the habituation method in fostering early childhood morals in Sumber Agung Village RT 03/RW 001, Pringsewu Regency. Against the background of limited resources and the influence of the external environment, the urgency of this research lies in the need for concrete strategies to assist families in creating effective and relevant habituation patterns for early childhood development. This research used a qualitative approach with a case study method. Data were collected through in-depth interviews with families, direct observation of daily interactions, and document analysis such as family diaries and moral education materials used. Data were analyzed thematically to identify patterns of habituation, values instilled, and challenges faced by the family. This approach allows the research to explore an in-depth understanding of the dynamics of moral development in the unique social, cultural and economic context of Sumber Agung Village. The results show that the habituation method is implemented through five main strategies: consistency, patience, creativity, collaboration, and supervision. Activities such as praying in congregation, sharing, maintaining cleanliness, and respecting others become part of the routine taught to children. This habit is strengthened by parental exemplary, creative methods, and collaborative support between family and environment. As a result, children show significant moral development, such as discipline, responsibility and empathy. This research confirms the importance of the family's role in fostering early childhood morals, with results that contribute to the development of moral education strategies in rural communities.